Pharmacognostical Evaluation of Bhringaraja (Eclipta alba Hassk): An Ayurvedic Drug (International Journal of Ayurveda and Pharma Research, 2025)
This study explores the pharmacognostical properties of Bhringaraja (Eclipta alba Hassk) churna, an herb highly valued in Ayurvedic medicine for its therapeutic benefits. The primary aim is to authenticate the identity of Bhringaraja churna and assess its quality parameters through comprehensive macroscopic, microscopic, and physicochemical, phytochemical evaluations. Macroscopic Analysis: The macroscopic examination confirmed the characteristic features of Bhringaraja, such as its yellowish-brown color, fine texture, and characteristic earthy aroma and bitter taste. Microscopic Analysis: Leaf microscopy showed upper and lower epidermis, cuticle, hypodermis, collenchyma, simple trichome, vascular bundle phloem, proto and meta xylem. Affirming the herb's identity and physicochemical parameters: Various physicochemical parameters were measured, including moisture content, ash values, extract values, and pH. These parameters ensure the stability, and quality of the Churna. This study underscores the importance of pharmacognostical and phytochemical research in enhancing the understanding and application of traditional herbal medicines in contemporary healthcare.